Modeling Accounting for the Restoration Process of War-Damaged Fixed Assets - Krupka, Yaroslav; Pasternak, Ihor; Pasternak, Yurii (Herald of Economics, 2026)
The article examines the principles and rules for accounting for losses from destruction or damage to property of enterprises and institutions, to analyze alternative approaches to accounting for the process of restoring damaged fixed assets, as well as the forms and accounting treatment of financial sources used to cover such costs and losses, using the modeling method. To achieve the research objectives, systemic and innovative approaches to the collection and generalization of accounting information were applied, along with methods of bibliographic and conceptual analysis, modeling of economic processes, and modeling of alternative accounting treatments. The study reveals the specifics of organizing and documenting transactions in the course of inventory control over losses incurred due to the destruction of fixed assets of enterprises. Various accounting options for the process of restoring damaged property or writing off assets that are not subject to restoration are outlined using the modeling method. The forms and accounting treatment of the financial support required for these processes—through own funds, borrowings, charitable assistance, and transactions involving the transfer of fixed assets to meet the needs of the Armed Forces of Ukraine (AFU)—are examined. Further scientific research in this area is advisable to expand the information field regarding economic processes related to the restoration of damaged property, the search for financial sources, and their informational presentation through the modeling of accounting processes.